Predictive Value of Tumor ERCC1 Expression for Treatment Outcomes After Adjuvant Chemotherapy in Patients with Completely Resected Non-Small Cell Lung Cancer - Nakata M; Saisho S; Soh J; Okumura N; Nakamura H; Yamashita M; Toyooka S; Date H (Cancer Management and Research)
Masao Nakata,1 Shinsuke Saisho,1 Junichi Soh,2 Norihito Okumura,3 Hiroshige Nakamura,4 Motohiro Yamashita,5 Shinichi Toyooka,2 Hiroshi Date6 1Department of General Thoracic Surgery, Kawasaki Medical School, Kurashiki, Okayama, Japan; 2Department of General Thoracic Surgery and Breast and Endocrinological Surgery, Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, Okayama, Japan; 3Department of Thoracic Surgery, Kurashiki Central Hospital, Kurashiki, Okayama, Japan; 4Division of General Thoracic Surgery and Breast and Endocrine Surgery, Department of Surgery, Faculty of Medicine, Tottori University, Yonago, Tottori, Japan; 5Department of Thoracic Surgery, National Hospital Organization Shikoku Cancer Center, Matsuyama, Ehime, Japan; 6Department of Thoracic Surgery, Kyoto University Graduate School of Medicine, Kyoto, JapanCorrespondence: Masao Nakata, Department of General Thoracic Surgery, Kawasaki Medical School, Matsushima 577, Kurashiki, Okayama, 701-0192, Japan, Tel +81-86-462-1111, Fax +81-86-462-1199, Email mnakata@med.kawasaki-m.ac.jpPurpose: To evaluate the predictive value of tumor expression of the excision repair cross-complementation group 1 gene (ERCC1) for the treatment outcomes after platinum-based adjuvant chemotherapy in patients with completely resected non-small cell lung cancer (NSCLC).Methods: In this study, we conducted immunohistochemical analysis using a mouse monoclonal anti-ERCC1 antibody (clone 8F1) of operative specimens obtained from 238 patients enrolled in the SLCG0401 study which compared paclitaxel plus carboplatin (CBDCA+PTX) with uracil-tegafur (UFT) as adjuvant chemotherapy for stage IB-IIIA NSCLC. The overall survival (OS) of the patients was compared according to the ERCC1 expression status and adjuvant chemotherapy employed.Results: Of the 238 specimens, 102 (42.9%) showed a positive result for ERCC1 expression. There were no significant differences in the patient characteristics or OS between the tumor ERCC1-positive and -negative patient groups. Among the patients with ERCC1-negative tumors, there was no significant difference in the survival between patient groups treated with CBDCA+PTX and UFT (HR=0.932, 95% CI: 0.52– 1.67, p=0.814). However, among the patients with ERCC1-positive tumors, CBDCA+PTX treatment tended to yield an inferior outcome, in terms of the OS, as compared with UFT treatment (HR=1.852, 95% CI: 0.92– 3.73, p=0.080). Multivariate analysis showed that ERCC1 expression was not an independent predictor of the OS following CBDCA+PTX treatment in completely resected NSCLC patients.Conclusion: In completely resected NSCLC patients with positive tumor ERCC1 expression, adjuvant CBDCA+PTX treatment tended to yield an inferior outcome as compared with UFT treatment in terms of the OS. However, immunohistochemical analysis with the 8F1 antibody cannot be used for clinical decision making at this point.Keywords: non-small cell lung cancer, postoperative adjuvant chemotherapy, platinum-based chemotherapy, excision repair cross-complementation group 1 gene, survival